Film-shaped adhesive, adhesive film, connection structure, and method for producing connection structure
The film-like adhesive, formulated with thermoplastic resin and radical polymerizable compounds, addresses the challenge of achieving sufficient adhesive strength and tamperability in circuit connections by utilizing a specific dynamic viscoelasticity profile, enhancing the efficiency of rework processes.
Patent Information
- Application Number
- JP2023145153
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-19
AI Technical Summary
Existing circuit connection adhesives face challenges in achieving sufficient adhesive strength while maintaining excellent tamperability and workability, particularly during rework processes where misalignment can occur.
A film-like adhesive comprising a thermoplastic resin and a radical polymerizable compound, with a specific dynamic viscoelasticity profile characterized by multiple maximum loss tangent values, is used to create a connection structure that balances adhesion and tamperability.
The adhesive exhibits excellent tamperability and reworkability, maintaining sufficient adhesive strength while allowing for easy reattachment during rework processes, thus improving the efficiency of circuit connection manufacturing.
Smart Images

Figure 2025038510000005 
Figure 2025038510000006 
Figure 2025038510000007
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a film-like adhesive, an adhesive film, a connection structure, and a method for manufacturing a connection structure. [Background technology]
[0002] Thermosetting resins using epoxy resins that are highly adhesive and highly reliable are known as circuit connecting materials for semiconductor elements and liquid crystal display elements (see, for example, Patent Document 1). The resin components generally used are epoxy resins, curing agents such as phenolic resins that are reactive with epoxy resins, and latent curing agents that promote the reaction between the epoxy resin and the curing agent. The latent curing agent is an important factor that determines the curing temperature and curing speed, and various compounds are used from the viewpoints of storage stability at room temperature and curing speed when heated.
[0003] Recently, radical curing adhesives that use acrylate derivatives and / or methacrylate derivatives (hereinafter collectively referred to as "(meth)acrylate derivatives") in combination with peroxides, which are radical polymerization initiators, have been attracting attention. Radical curing allows for rapid curing because radicals, which are reactive species, are highly reactive (see, for example, Patent Documents 2 and 3). For this reason, rapid curing adhesives, which are advantageous in shortening production time, are currently becoming more widespread. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 1-113480 [Patent Document 2] JP 2002-203427 A [Patent Document 3] International Publication No. 98 / 044067 Brochure Summary of the Invention [Problem to be solved by the invention]
[0005] Incidentally, an adhesive for circuit connection is required to be able to bond circuit components together with sufficient adhesive strength, but it is also desirable for the adhesive to have excellent temporary attachment properties in order to deal with the following problems. When connecting circuit components together, a process may be applied in which a film-like adhesive is applied to one circuit component by pressure attachment and then the other circuit component is placed in a predetermined position and then thermocompression bonded. In such a method, if the adhesive is misaligned, a rework operation may be required in which the adhesive is peeled off and a new adhesive is temporarily attached again. However, if the adhesive has too high adhesion to the circuit components, the rework operation may be difficult, and if the adhesion is too low, problems such as the adhesive falling off during the temporary attachment operation may occur.
[0006] Therefore, the present disclosure aims to provide a film-like adhesive that has excellent temporary attachment properties and can exhibit sufficient adhesive strength, an adhesive film containing the same, and a method for manufacturing a connection structure and a connection structure using the same. [Means for solving the problem]
[0007] One aspect of the present disclosure relates to a method for manufacturing a connection structure as follows. [1] A step of laminating an adhesive film on a surface of a first circuit member having a first electrode, the surface having the first electrode formed thereon; a step of disposing a second circuit member having a second electrode on the first circuit member laminated with the adhesive film such that the first electrode and the second electrode face each other, and bonding them by thermocompression to electrically connect the first electrode and the second electrode to each other; The adhesive film has a film-like adhesive containing a thermoplastic resin and a radical polymerizable compound, A method for producing a connection structure, wherein the film-like adhesive has a waveform of loss tangent (tan δ) having multiple maximum values obtained by dynamic viscoelasticity measurement after heating at 170°C for 5 seconds. [2] The method for producing a connection structure according to the above [1], wherein the waveform of the loss tangent (tan δ) has a maximum value between 40°C and 90°C. [3] The method for producing a connection structure described in [1] or [2] above, wherein the waveform of the loss tangent (tan δ) has two maxima between 40°C and 100°C, and the difference between the temperatures showing the two maxima is 20°C or more and 50°C or less. [4] The method for producing a connection structure according to any one of the above [1] to [3], wherein the thermoplastic resin contains a polyester urethane resin and a phenoxy resin. [5] The method for producing a connection structure according to any one of the above [1] to [4], wherein the radically polymerizable compound contains a (poly)urethane (meth)acrylate compound.
[0008] Moreover, one aspect of the present disclosure relates to the following film-like adhesive and adhesive film. [6] A film-like adhesive containing a thermoplastic resin and a radically polymerizable compound, wherein the waveform of loss tangent (tan δ) obtained by dynamic viscoelasticity measurement after heating at 170°C for 5 seconds has multiple maximum values. [7] The film-like adhesive described in [6] above, wherein the waveform of the loss tangent (tan δ) has a maximum value between 40°C and 90°C. [8] The film-like adhesive described in [6] or [7] above, wherein the waveform of the loss tangent (tan δ) has two maximum values between 40°C and 100°C, and the difference between the temperatures showing the two maximum values is 20°C or more and 50°C or less. [9] The film-like adhesive according to any one of the above [6] to [8], wherein the thermoplastic resin contains a polyester urethane resin and a phenoxy resin.
[10] The film-like adhesive according to any one of the above [6] to [9], wherein the radically polymerizable compound contains a (poly)urethane (meth)acrylate compound.
[11] The film-like adhesive according to any one of the above [6] to
[10] , further comprising conductive particles.
[12] An adhesive film comprising the film-like adhesive according to any one of [6] to
[11] above.
[13] The adhesive film described in
[12] above, comprising a first adhesive layer made of the film-like adhesive and a second adhesive layer made of an adhesive composition containing conductive particles.
[0009] Moreover, one aspect of the present disclosure relates to the following connection structure.
[14] A connection structure comprising: a first circuit member having a first electrode; a second circuit member having a second electrode; and a connection portion disposed between the first circuit member and the second circuit member and electrically connecting the first electrode and the second electrode to each other, wherein the connection portion comprises a cured product of the film-like adhesive described in
[12] or
[13] above. Effect of the Invention
[0010] According to the present disclosure, it is possible to provide a film-like adhesive that has excellent temporary attachment properties and can exhibit sufficient adhesive strength, an adhesive film comprising the same, and a method for manufacturing a connection structure and a connection structure using the same. [Brief description of the drawings]
[0011] [Figure 1] FIG. 13 is a diagram for explaining the waveform of a loss tangent (tan δ). [Diagram 2] FIG. 2 is a schematic cross-sectional view showing one embodiment of an adhesive film. [Diagram 3] FIG. 1 is a schematic cross-sectional view showing one embodiment of a connection structure. [Figure 4] 4A to 4C are schematic cross-sectional views showing a method for manufacturing the connection structure of FIG. 3. [Diagram 5] FIG. 13 is a diagram showing an example of a binarized image of a temporarily pressed body photographed by a differential interference contrast microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] In this specification, the numerical range indicated by "~" indicates a range including the numerical values described before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a certain stage of the numerical range may be replaced with the upper limit or lower limit of the numerical range of another stage. In the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in the examples. In addition, the upper limit and lower limit values described individually can be arbitrarily combined. In this specification, "(meth)acrylate" means at least one of acrylate and the corresponding methacrylate. The same applies to other similar expressions such as "(meth)acryloyl". In addition, "(poly)" means both the case with and without the prefix "poly". In addition, "A or B" may include either A or B, or may include both. In addition, the materials exemplified below may be used alone or in combination of two or more types, unless otherwise specified. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified.
[0013] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the drawings where necessary. However, the present disclosure is not limited to the following embodiments.
[0014] <Film adhesive> The film-like adhesive of this embodiment contains (A) a thermoplastic resin (hereinafter also referred to as "(A) component") and (B) a radically polymerizable compound (hereinafter also referred to as "(B) component"), and the waveform of the loss tangent (tan δ) obtained by dynamic viscoelasticity measurement after heating at 170°C for 5 seconds has multiple maximum values. The film-like adhesive of this embodiment is excellent in temporary attachment and reworkability and can exhibit sufficient adhesive strength. It is presumed that such effects are obtained for the following reasons. It is considered that the adhesive showing the above waveform has poor polymer compatibility in the cured product, and it is presumed that sufficient adhesive strength can be ensured even in a formulation that takes adhesion into consideration by being able to aggregate the polymer of the radically polymerizable compound, which is easy to obtain adhesive strength, into islands.
[0015] The dynamic viscoelasticity measurement can be carried out in the following manner. (i) A pre-heating sample is prepared by laminating a film-like adhesive to a thickness of about 100 μm. The thickness of each film-like adhesive to be laminated can be 5 to 50 μm. (ii) The pre-heated sample prepared in (i) is thermally cured using a thermocompression bonding machine "FCB3" (product name, manufactured by Panasonic) under the following conditions: backup temperature 90°C, set pressure 100N, ultimate temperature 170°C, heating time 5 seconds, to prepare a measurement sample. (iii) The measurement sample obtained in (ii) is set in a dynamic viscoelasticity measuring device "RSA-G2" (product name, manufactured by TA Instruments), and dynamic viscoelasticity is measured under the conditions of tensile mode, measurement frequency of 0.1 Hz, strain of 0.1%, heating rate of 10°C / min, and measurement temperature range of 0°C to 200°C.
[0016] The waveform of the loss tangent (tan δ) refers to the relationship between the temperature and the loss tangent (tan δ) obtained by the above measurement. In addition, in this disclosure, the terms used for the waveform of the loss tangent (tan δ) are defined as follows. Note that FIG. 1 is a diagram for explaining the waveform of the loss tangent (tan δ). tan δ peak top: The point where the increase or decrease in tan δ changes from an increase to a decrease (PT 1 and P.T.2 ), where an increase means that tan δ increases continuously by 5°C or more. Tan δ peak bottom: The point where the increase or decrease in tan δ changes from a decrease to an increase (PB in Figure 1). 1 ), where a decrease means that tan δ decreases continuously for 5°C or more. Temperature difference between the tan δ peak tops: The difference between the temperature of the tan δ peak top on the high-temperature side and the temperature of the tan δ peak top on the low-temperature side (D in Figure 1) 1 ) Difference in tan δ between the tan δ peak bottom and the tan δ peak top: The difference between the tan δ of the tan δ peak top with smaller tan δ and the tan δ of the tan δ peak bottom (D in Figure 1) 2 )
[0017] In the film-like adhesive of this embodiment, from the viewpoint of compatibility, the waveform of the loss tangent (tan δ) may have two maximum values, that is, may have a bimodal nature. In this case, from the viewpoint of more clearly defining the peak shape, the tan δ difference (intensity difference) between the tan δ peak bottom and the tan δ peak top may be 0.02 or more, and from the viewpoint of the tan δ waveform having a bimodal nature, the temperature difference between the tan δ peak tops may be within 50 ° C., or may be 20 ° C. or more and 50 ° C. or less. In addition, the temperature of the tan δ peak top on the low temperature side may be 40 ° C. or more and 70 ° C. or less, and the temperature of the tan δ peak top on the high temperature side may be 70 ° C. or more and 100 ° C. or less.
[0018] From the standpoint of storage stability, the film-like adhesive of this embodiment may have a waveform of loss tangent (tan δ) that has a maximum value between 40°C and 90°C, and from the standpoints of compatibility and storage stability, the waveform of loss tangent (tan δ) may have two maximum values between 40°C and 100°C, with the difference between the temperatures showing the two maximum values being 20°C or more and 50°C or less.
[0019] In addition, methods for making the waveform of the loss tangent (tan δ) satisfy the above conditions (e.g., bimodality, temperature range of the tan δ peak top, temperature difference between the tan δ peak tops, tan δ difference between the tan δ peak bottom and the tan δ peak top) include combining two or more of the following. (i) Two or more types of component (A) are mixed and their mixing ratio is adjusted. (ii) The mixing ratio of component (A) and component (B) is adjusted. For example, in the case of (ii), the content of the (B) component may be adjusted to 70 to 80 parts by mass per 100 parts by mass of the (A) component. As an example of a combination, for example, the content of the (B) component may be adjusted to more than 80 parts by mass per 100 parts by mass of the (A) component, and the blending ratio of the (A1) component and the (A2) component described below [(A1) / (A2)]] may be adjusted to be smaller than 1 / 2.
[0020] The film-like adhesive of the present embodiment can be used, for example, as a member that constitutes the adhesive layer in an adhesive film (adhesive film for circuit connection) used in the following method. A method for manufacturing a connection structure, comprising the steps of: laminating an adhesive film on a surface of a first circuit member having a first electrode (e.g., a first circuit member having a first circuit electrode formed on a main surface of a first substrate) on which the first electrode is formed; and placing a second circuit member having a second electrode (e.g., a second circuit member having a second circuit electrode formed on a main surface of a second substrate) on the first circuit member laminated with the adhesive film so that the first electrode and the second electrode face each other, and thermocompression bonding them to electrically connect the first electrode and the second electrode to each other.
[0021] [Component (A): Thermoplastic resin] The component (A) may be one or more resins selected from polyimide resin, polyamide resin, phenoxy resin, poly(meth)acrylic resin, polyester resin, polyurethane resin, polyesterurethane resin, and polyvinyl butyral resin. In order to easily obtain multiple maximum values in the waveform of the loss tangent (tan δ), two or more of the above thermoplastic resins may be contained, or two or more thermoplastic resins having different Tg may be contained. Examples of the combination of resins include a combination of a phenoxy resin and a poly(meth)acrylic resin, a combination of a phenoxy resin and a polyester resin, a combination of a phenoxy resin and a polyesterurethane resin, and a combination of a phenoxy resin and a polyimide resin.
[0022] The polyester resin may be a polyethylene naphthalate resin from the viewpoint of blending a resin having a higher Tg. The polyethylene naphthalate resin can be obtained by transesterification and polycondensation reaction of a naphthalenedicarboxylic acid ester with diethylene glycol, or by direct polymerization of naphthalenedicarboxylic acid with diethylene glycol. The phenoxy resin can be obtained by reacting a bifunctional phenol with an epihalohydrin to a high molecular weight, or by polyaddition reaction of a bifunctional epoxy resin with a bifunctional phenol.
[0023] The film-like adhesive of this embodiment may contain a rubber component as component (A). Examples of the rubber component include silicone rubber, acrylic rubber, polyisoprene rubber, polybutadiene rubber, carboxyl-terminated polybutadiene rubber, hydroxyl-terminated polybutadiene rubber, 1,2-polybutadiene rubber, carboxyl-terminated 1,2-polybutadiene rubber, hydroxyl-terminated 1,2-polybutadiene rubber, styrene-butadiene rubber, hydroxyl-terminated styrene-butadiene rubber, acrylonitrile-butadiene rubber, carboxylated nitrile rubber, hydroxyl-terminated poly(oxypropylene) rubber, alkoxysilyl-terminated poly(oxypropylene) rubber, poly(oxytetramethylene) glycol rubber, polyolefin glycol rubber, and poly-ε-caprolactone rubber.
[0024] From the viewpoint of obtaining a resin system with different compatibility, the film-like adhesive of this embodiment may contain a polyester urethane resin (hereinafter also referred to as "component (A1)") and a phenoxy resin (hereinafter also referred to as "component (A2)") as thermoplastic resins.
[0025] From the viewpoint of increasing the tan δ (intensity) of the tan δ peak top on the low temperature side and making it easier to manifest bimodality, the mass ratio of the component (A2) to the component (A1) [(A2) / (A1)] may be 2 or more and 2.5 or less.
[0026] The weight average molecular weight of the thermoplastic resin may be 5,000 or more, or 10,000 or more, from the viewpoint of film formability, may be 80,000 or less, or 150,000 or less, from the viewpoint of adhesiveness, and may be 5,000 to 150,000, or 10,000 to 80,000, from the viewpoint of adhesiveness and film formability. The weight average molecular weight of the thermoplastic resin means the weight average molecular weight (standard polystyrene equivalent value) measured by GPC (gel permeation chromatography).
[0027] In the present disclosure, the thermoplastic resin having a radically polymerizable functional group is blended as the radically polymerizable compound (B).
[0028] From the viewpoint of film formability, the content of component (A) in the film adhesive may be 20 mass % or more or 30 mass % or more, and may be 60 mass % or less or 50 mass % or less, or may be 20 to 60 mass % or 30 to 50 mass %, based on the resin components of the film adhesive (e.g., components other than conductive particles and filler).
[0029] The content of the (A) component, relative to 100 parts by mass of the combined total of the (A) component and the (B) component, may be 30 parts by mass or more, 40 parts by mass or more, or 50 parts by mass or more, and may be 90 parts by mass or less, 70 parts by mass or less, or 60 parts by mass or less, or may be 50 to 60 parts by mass.
[0030] [Component (B): radically polymerizable compound] The (B) component can be a compound having a radically polymerizable functional group. Examples of the radically polymerizable functional group include a vinyl group, an acryloyl group, and a methacryloyl group. Of these, a compound having an acryloyl group and / or a methacryloyl group can be used. The (B) component can be used alone or in combination of two or more types.
[0031] As the component (B), the compound described below can be used in either a monomeric or oligomeric state, and it is also possible to use a monomeric and oligomeric form in combination.
[0032] The (B) component is a polyfunctional (meth)acrylate compound having two or more (meth)acryloyloxy groups. Examples of such (meth)acrylate compounds include epoxy (meth)acrylate, urethane (meth)acrylate, polyether (meth)acrylate, polyester (meth)acrylate, trimethylolpropane tri(meth)acrylate, polyalkylene glycol di(meth)acrylate such as polyethylene glycol di(meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, neopentyl glycol di(meth)acrylate, dipentaerythritol hexa(meth)acrylate, isocyanuric acid modified bifunctional (meth)acrylate, and isocyanuric acid modified trifunctional (meth)acrylate. Examples of epoxy (meth)acrylates include epoxy (meth)acrylates in which (meth)acrylic acid is added to two glycidyl groups of bisphenol fluorene diglycidyl ether, and compounds in which a (meth)acryloyloxy group is introduced into a compound in which ethylene glycol and / or propylene glycol are added to two glycidyl groups of bisphenol fluorene diglycidyl ether, etc. These compounds may be used alone or in combination of two or more.
[0033] Among the above (meth)acrylate compounds, a (poly)urethane (meth)acrylate compound can be used from the viewpoint of obtaining better adhesiveness by having a urethane bond. The content of the (poly)urethane (meth)acrylate compound may be 30 to 90 mass%, 40 to 80 mass%, or 50 to 70 mass% based on the total mass of the (B) component from the viewpoint of obtaining better adhesiveness.
[0034] From the viewpoint of improving heat resistance, the component (B) can be one having at least one partial structure selected from the group consisting of a dicyclopentane skeleton, a tricyclodecane skeleton, and a triazine ring.
[0035] Furthermore, from the viewpoint of further improving heat resistance, the (B) component may contain a (meth)acrylate compound having a tricyclodecane skeleton. The content of the (meth)acrylate compound having a tricyclodecane skeleton may be 2 to 20 mass%, 2 to 15 mass%, or 2 to 10 mass% based on the total mass of the (B) component.
[0036] From the viewpoint of obtaining even better adhesiveness, the film-like adhesive may contain a monofunctional (meth)acrylate compound as component (B). Examples of the monofunctional (meth)acrylate compound include pentaerythritol (meth)acrylate, 2-cyanoethyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-hexyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, isobornyl (meth)acrylate, isodecyl (meth)acrylate, and the like. Examples of the glycidyl group-containing (meth)acrylate include (meth)acryloylmorpholine and (meth)acrylates obtained by reacting one of the glycidyl groups of an epoxy resin having a plurality of glycidyl groups with (meth)acrylic acid. These compounds may be used alone or in combination of two or more.
[0037] From the viewpoint of obtaining even better adhesiveness, the film adhesive may contain, as component (B), a compound having a radically polymerizable functional group such as an allyl group, a maleimide group, a vinyl group, etc. Examples of such compounds include N-vinylimidazole, N-vinylpyridine, N-vinylpyrrolidone, N-vinylformamide, N-vinylcaprolactam, 4,4'-vinylidenebis(N,N-dimethylaniline), N-vinylacetamide, N,N-dimethylacrylamide, N-isopropylacrylamide, and N,N-diethylacrylamide.
[0038] For the purpose of improving adhesive strength, the film adhesive may contain a radical polymerizable compound having a phosphoric acid ester structure as component (B). The radical polymerizable compound having a phosphoric acid ester structure may be, for example, a compound represented by the following formula (1), (2), or (3). [ka] In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents a (meth)acryloyloxy group, and a and b each independently represent an integer of 1 to 8. 1 , R 2 , a and b may be the same or different.
[0039] [ka] In formula (2), R 3 represents a (meth)acryloyloxy group, and c and d each independently represent an integer of 1 to 8. 3 , c and d may be the same or different.
[0040] [ka] In formula (3), R 4 represents a hydrogen atom or a methyl group, R 5 represents a (meth)acryloyloxy group, and e and f each independently represent an integer of 1 to 8. 4 , R 4 , e and f may be the same or different.
[0041] Examples of radical polymerizable compounds having a phosphate ester structure include acid phosphooxyethyl (meth)acrylate, acid phosphooxypropyl (meth)acrylate, acid phosphooxypolyoxyethylene glycol mono(meth)acrylate, acid phosphooxypolyoxypropylene glycol mono(meth)acrylate, 2,2'-di(meth)acryloyloxydiethyl phosphate, EO (ethylene oxide)-modified phosphate di(meth)acrylate, phosphoric acid-modified epoxy (meth)acrylate, and vinyl phosphate.
[0042] The content of component (B) in the film-like adhesive may be 10 parts by mass or more, 30 parts by mass or more, or 40 parts by mass or more, and may be 70 parts by mass or less, 60 parts by mass or less, or 50 parts by mass or less, or may be 40 to 50 parts by mass, relative to 100 parts by mass of the combined amount of components (A) and (B).
[0043] In order to make the waveform of the loss tangent (tan δ) bimodal, the ratio of the content of the component (B) to the content of the component (A) [(B) / (A)] may be 0.7 to 0.8. When (B) / (A) exceeds 0.8, the mass ratio of the component (A2) to the component (A1) [(A2) / (A1)] can be 2 or greater.
[0044] When the film-like adhesive contains a radically polymerizable compound having a phosphate ester structure as component (B), the content of the radically polymerizable compound having a phosphate ester structure may be 1 part by mass or more, or may be 100 parts by mass or less, 50 parts by mass or less, or 10 parts by mass or less, per 100 parts by mass of the combined amount of components (a) and (b).
[0045] The film-like adhesive of this embodiment may further contain at least one of (C) a radical polymerization initiator (hereinafter also referred to as "component (C)"), (D) a filler (hereinafter also referred to as "component (D)"), (E) a silane coupling agent (hereinafter also referred to as "component (E)"), and (F) conductive particles (hereinafter also referred to as "component (F)").
[0046] [Component (C): Radical polymerization initiator] The component (C) can be arbitrarily selected from compounds such as peroxides and azo compounds. From the viewpoint of excellent stability, reactivity and compatibility, the component (C) is preferably a peroxide having a one-minute half-life temperature of 90°C to 175°C and a molecular weight of 180 to 1000. The "one-minute half-life temperature" means the temperature at which the half-life of the peroxide is one minute. The "half-life" means the time until the concentration of a compound at a given temperature decreases to half of its initial value.
[0047] Examples of the radical polymerization initiator include 1,1,3,3-tetramethylbutyl peroxyneodecanoate, di(4-t-butylcyclohexyl) peroxydicarbonate, di(2-ethylhexyl) peroxydicarbonate, cumyl peroxyneodecanoate, 1,1,3,3-tetramethylbutyl peroxyneodecanoate, dilauroyl peroxide, 1-cyclohexyl-1-methylethyl peroxyneodecanoate, t-hexyl peroxyneodecanoate, t-butyl peroxyneodecanoate, t- Butyl peroxypivalate, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, 2,5-dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane, t-hexylperoxy-2-ethylhexanoate, t-butylperoxy-2-ethylhexanoate, t-butylperoxyneoheptanoate, t-amylperoxy-2-ethylhexanoate, di-t-butylperoxyhexahydroterephthalate, t-amylperoxy-3,5,5-trimethylhexanoate, 3 -Hydroxy-1,1-dimethylbutyl peroxyneodecanoate, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, t-amyl peroxyneodecanoate, t-amyl peroxy-2-ethylhexanoate, 3-methylbenzoyl peroxide, 4-methylbenzoyl peroxide, di(3-methylbenzoyl) peroxide, dibenzoyl peroxide, di(4-methylbenzoyl) peroxide, 2,2'-azobis-2,4-dimethylvaleronitrile, 1,1'-azobis (1-acetoxy-1-phenylethane), 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), dimethyl-2,2'-azobisisobutyronitrile, 4,4'-azobis(4-cyanovaleric acid), 1,1'-azobis(1-cyclohexanecarbonitrile), t-hexylperoxyisopropyl monocarbonate, t-butylperoxymaleic acid, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxylaurate, 2,5-dimethyl-2,The compound may be one or more compounds selected from 5-di(3-methylbenzoylperoxy)hexane, t-butylperoxy-2-ethylhexyl monocarbonate, t-hexylperoxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-butylperoxybenzoate, dibutylperoxytrimethyladipate, t-amylperoxynormaloctoate, t-amylperoxyisononanoate, and t-amylperoxybenzoate.
[0048] The content of component (C) in the film-like adhesive may be 1 part by mass or more, or 2.5 parts by mass or more, and may be 15 parts by mass or less, 10 parts by mass or less, or 5 parts by mass or less, per 100 parts by mass of the combined amount of components (A) and (B).
[0049] [(D) Component: Filler] The filler may be particles composed of silicon, calcium, zirconium, titanium, aluminum, carbon, bismuth, cobalt, copper, iron, indium, manganese, tin, yttrium, zinc, etc., or compounds containing these, organic compounds, etc. The average particle size of the particles is, for example, 0.005 μm to 25 μm.
[0050] The content of component (D) in the film-like adhesive may be 1 part by mass or more, or 5 parts by mass or more, and may be 30 parts by mass or less, 25 parts by mass or less, or 20 parts by mass or less, per 100 parts by mass of the combined amount of components (A) and (B).
[0051] [Component (E): Silane coupling agent] Examples of the silane coupling agent include vinyltrimethoxysilane, vinyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, 3-ureidopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, and condensates thereof.
[0052] The content of component (E) in the film-like adhesive may be 0.1 parts by mass or more, 0.2 parts by mass or more, or 0.25 parts by mass or more, and may be 10 parts by mass or less, or 5 parts by mass or less, relative to 100 parts by mass of the combined amount of components (A) and (B).
[0053] [(F) Component: Conductive particles] Examples of the (F) component include metal particles such as Au, Ag, Ni, Cu, solder, and conductive particles such as conductive carbon particles. The conductive particles may be coated conductive particles having a core made of non-conductive glass, ceramic, plastic, or other particles, and a layer made of the above metal, metal particles, conductive carbon particles, or the like, that covers the core. The conductive particles may be insulating coated conductive particles having the above-mentioned conductive particles and an insulating coating layer formed of an insulating material such as a polymer resin that covers the surface of the conductive particles, from the viewpoint of preventing short circuits between the conductive particles and improving the insulation between adjacent circuit electrodes, particularly when the amount of the conductive particles is increased. These conductive particles, coated conductive particles, and insulating coated conductive particles may be used alone or in combination of two or more.
[0054] The average particle size of the conductive particles may be 1 μm to 50 μm from the viewpoint of excellent dispersibility and conductivity. The content of the conductive particles may be 0.1 vol% or more, 30 vol% or less, or 10 vol% or less based on the total volume of the film-like adhesive. The content of the conductive particles is determined based on the volume of each component of the adhesive (before curing) at 23°C. The volume of each component can be, for example, a value converted from weight to volume using specific gravity. In addition, for example, the component can be poured into a measuring cylinder or the like containing an appropriate solvent (water, alcohol, etc.) that thoroughly wets the component without dissolving or swelling the component, and the increased volume can be determined as the volume.
[0055] The film-like adhesive of the present embodiment may contain other additives such as other resins such as phenolic resins and melamine resins, softeners, curing accelerators, antiaging agents, colorants, flame retardants, thixotropic agents, adhesion improvers, thickeners, leveling agents, weather resistance improvers, polymerization inhibitors, etc. Examples of polymerization inhibitors include hydroquinone and methyl ether hydroquinones.
[0056] The film-like adhesive of this embodiment can be produced by the following method. Specifically, first, the above-mentioned components and other components added as necessary are added to a solvent (organic solvent), and dissolved or dispersed by stirring, mixing, kneading, etc. to prepare a varnish composition (varnish-like adhesive composition). Thereafter, the varnish composition is applied to a substrate that has been subjected to a release treatment using a knife coater, roll coater, applicator, comma coater, die coater, etc., and the solvent is volatilized by heating to form a film-like adhesive on the substrate.
[0057] The solvent used in preparing the varnish composition may be a solvent that has the property of dissolving or dispersing each component uniformly. Examples of such solvents include toluene, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, propyl acetate, and butyl acetate. These solvents can be used alone or in combination of two or more. The stirring and mixing and kneading in preparing the varnish composition can be performed using, for example, a stirrer, a grinding machine, a three-roll mill, a ball mill, a bead mill, or a homodisper.
[0058] The substrate is not particularly limited as long as it has heat resistance sufficient to withstand the heating conditions for volatilizing the solvent. For example, substrates (e.g., films) made of oriented polypropylene (OPP), polyethylene terephthalate (PET), polyethylene naphthalate, polyethylene isophthalate, polybutylene terephthalate, polyolefin, polyacetate, polycarbonate, polyphenylene sulfide, polyamide, polyimide, cellulose, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinylidene chloride, synthetic rubber, liquid crystal polymer, etc. can be used.
[0059] The heating conditions for volatilizing the solvent from the varnish composition applied to the substrate may be conditions that allow the solvent to volatilize sufficiently, for example, at 40° C. or higher and 120° C. or lower for 0.1 minutes or longer and 10 minutes or shorter.
[0060] In the film-like adhesive of the present embodiment, a portion of the solvent may remain unremoved. The content of the solvent in the film-like adhesive of the present embodiment may be, for example, 10 mass % or less, or 5 mass % or less, based on the total mass of the film-like adhesive.
[0061] From the viewpoint of temporary attachment properties, the film-like adhesive of this embodiment may have an adhesion rate of 45 to 60% as measured by the following method. 1.1.2 mm wide slit film adhesive is applied to a 0.7 mm thick SiN xA substrate (a glass substrate and a silicon nitride (SiN x ) and then cover the adhesive with three sheets of silicone film (thickness 200 μm). 2. Following step 1, the film-like adhesive is temporarily pressed onto the glass at 70°C, 1 MPa, and for 1 second to obtain a temporarily pressed body. 3. Photograph the temporarily bonded body from the glass side using a differential interference microscope "ECLIPSE L300" (Nikon Corporation). 4. The captured image is trimmed and binarized using a self-made program (programming language: python, using OpenCV (Intel, module name) for image processing). The trimming process is performed so that only the area where the film adhesive is in contact with the glass substrate remains, and the binarization process is performed so that the area where the adhesive is in close contact with the glass becomes black. 5. Based on the binarized image, calculate the area ratio of the black parts using the following formula, and use this as the contact ratio. Black area ratio (%) = [(number of pixels in black area) x 100] / (number of pixels in entire image)
[0062] If the adhesion rate is 45% or more, the adhesive is less likely to fall off during the temporary attachment work, and if the adhesion rate is 60% or less, if the adhesive becomes misaligned during the temporary attachment work, it becomes easy to perform rework work by peeling off the adhesive and temporarily attaching new adhesive again.
[0063] <Adhesive film> The adhesive film of this embodiment includes the film-like adhesive of this embodiment described above.
[0064] Fig. 2 is a schematic cross-sectional view showing an adhesive film according to one embodiment. As shown in Fig. 2, in one embodiment, the adhesive film 1 is composed of a single layer made of an adhesive component 2 and conductive particles 3 dispersed in the adhesive component 2. In one embodiment, the adhesive component 2 contains the above-mentioned components (A) and (B), as well as other components such as components (C) to (E).
[0065] The adhesive film 1 may be in an uncured state or in a partially cured state.
[0066] The thickness of the adhesive film 1 may be, for example, 3 μm or more, or 10 μm or more, and may be 30 μm or less, or 20 μm or less.
[0067] In one embodiment, the adhesive film of this embodiment may have a multi-layer structure including a first adhesive layer made of a film-like adhesive and a second adhesive layer made of an adhesive composition containing conductive particles. The conductive particles and adhesive composition constituting the second adhesive layer may be formed from the same components as those of the film-like adhesive of this embodiment described above.
[0068] The adhesive film may be an anisotropically conductive adhesive film (anisotropically conductive film), or may be a conductive adhesive film that does not have anisotropic conductivity.
[0069] <Connection structure> Another embodiment of the present disclosure is a connection structure comprising a first circuit member having a first electrode, a second circuit member having a second electrode, and a connection portion disposed between the first circuit member and the second circuit member and electrically connecting the first electrode and the second electrode to each other, wherein the connection portion includes a cured product of the above-mentioned film-like adhesive.
[0070] Fig. 3 is a schematic cross-sectional view showing one embodiment of a connection structure. As shown in Fig. 3, a connection structure 10 includes a first circuit member 4 and a second circuit member 5 facing each other, and a connection portion 6 connecting the first circuit member 4 and the second circuit member 5 between the first circuit member 4 and the second circuit member 5.
[0071] The first circuit member 4 includes a first circuit board 41 and a first electrode 42 formed on a main surface 41a of the first circuit board 41. The second circuit member 5 includes a second circuit board 51 and a second electrode 52 formed on a main surface 51a of the second circuit board 51.
[0072] There are no particular limitations on the first circuit member 4 and the second circuit member 5, so long as they are members on which electrodes that require electrical connection are formed. Examples of members on which electrodes are formed (circuit members, etc.) include inorganic substrates such as semiconductors, glass, and ceramics; polyimide substrates such as TCP, FPC, and COF; substrates on which electrodes are formed on films such as polycarbonate, polyester, and polyethersulfone; and printed wiring boards, and a combination of two or more of these may be used.
[0073] The connection portion 6 includes a cured product of the film-like adhesive, and contains an insulating material 7, which is a cured product of the adhesive component, and conductive particles 3. The conductive particles 3 may be disposed not only between the opposing first electrode 42 and second electrode 52, but also between the main surface 41a of the first circuit board 41 and the main surface 51a of the second circuit board 51. In the connection structure 10, the first electrode 42 and the second electrode 52 are electrically connected via the conductive particles 3. That is, the conductive particles 3 are in contact with both the first electrode 42 and the second electrode 52.
[0074] In the connection structure 10, the opposing first electrode 42 and second electrode 52 are electrically connected via conductive particles 3, but if the film-like adhesive does not contain conductive particles, the first electrode 42 and second electrode 52 may be in direct contact with each other.
[0075] <Method of Manufacturing Connection Structure> Another embodiment of the present disclosure is a method for manufacturing a connection structure, comprising the steps of laminating the adhesive film of the present embodiment described above onto a surface of a first circuit member having a first electrode on which the first electrode is formed, and placing a second circuit member having a second electrode on the first circuit member laminated with the adhesive film such that the first electrode and the second electrode face each other, and thermocompression bonding them to electrically connect the first electrode and the second electrode to each other.
[0076] FIG. 4 is a schematic cross-sectional view showing one embodiment of a method for producing a connection structure. As shown in FIG. 4(a), first, a first circuit member 4 and an adhesive film 1 are prepared. Next, the adhesive film 1 is laminated onto the main surface 41a of the first circuit member 4. When the adhesive film 1 is laminated on a substrate (not shown), the laminate is laminated onto the first circuit member 4 with the adhesive film 1 side of the substrate facing the first circuit member 4. When the adhesive film 1 has a multilayer structure including a first adhesive layer made of a film-like adhesive and a second adhesive layer made of an adhesive composition containing conductive particles, it is preferable to laminate the first adhesive layer side so as to contact the main surface 41a of the first circuit member 4.
[0077] In this embodiment, pressure may be applied in the directions of arrows A and B in Fig. 4(a) to temporarily attach the adhesive film 1 and the first circuit member 4 (see Fig. 4(b)). At this time, heat may be applied together with the pressure.
[0078] 4(c), a second circuit member 5 is further placed on the adhesive film 1 temporarily attached to the first circuit member 4 with the second electrode 52 facing the first circuit member 4 (i.e., the first electrode 42 and the second electrode 52 are arranged opposite each other, and the adhesive film 1 is interposed between the first circuit member 4 and the second circuit member 5). If the adhesive film 1 is laminated on a substrate (not shown), the substrate is peeled off and then the second circuit member 5 is placed on the adhesive film 1.
[0079] These are then thermocompressed in the directions of arrows A and B in Fig. 4(c), thereby hardening the adhesive film 1 and achieving a permanent connection that electrically connects the first electrode 42 and the second electrode 52 to each other. As a result, a connection structure 10 as shown in Fig. 3 is obtained.
[0080] According to the method for producing a connection structure of this embodiment, since the adhesive film has a film-like adhesive that has excellent temporary attachment properties and can exert sufficient adhesive strength, the connection structure can be produced efficiently. Furthermore, even if rework work such as re-temporary attachment is required, the adhesive can be peeled off with good workability. EXAMPLES
[0081] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0082] <Synthesis of polyester urethane resin (A1)) 48 parts by mass of isophthalic acid and 37 parts by mass of neopentyl glycol were put into a stainless steel autoclave equipped with a stirrer, a thermometer, a condenser, a vacuum generator, and a nitrogen gas inlet tube, and 0.02 parts by mass of tetrabutoxy titanate as a catalyst was further put in. Then, the temperature was raised to 220°C under a nitrogen stream, and the mixture was stirred for 8 hours. Then, the pressure was reduced to atmospheric pressure (760 mmHg), and the mixture was cooled to room temperature. This caused a white precipitate to precipitate. Next, the white precipitate was taken out, washed with water, and then vacuum dried to obtain a polyester polyol. The obtained polyester polyol was thoroughly dried, and then dissolved in MEK (methyl ethyl ketone), and put into a four-neck flask equipped with a stirrer, a dropping funnel, a reflux condenser, and a nitrogen gas inlet tube. In addition, dibutyltin dilaurate was added as a catalyst in an amount of 0.05 parts by mass relative to 100 parts by mass of polyester polyol, and 4,4'-diphenylmethane diisocyanate in an amount of 50 parts by mass relative to 100 parts by mass of polyester polyol was dissolved in MEK and added using a dropping funnel, and the mixture was stirred at 80°C for 4 hours to obtain the desired polyester urethane resin. The weight average molecular weight of the polyester urethane resin was 15,000. The weight average molecular weight was measured by gel permeation chromatography (GPC) using a calibration curve based on standard polystyrene under the following conditions. (Measurement conditions) Equipment: Tosoh Corporation GPC-8020 Detector: Tosoh RI-8020 Column: Gelpack GLA160S+GLA150SG2000Hhr manufactured by Resonac Corporation Solvent: Tetrahydrofuran Injection volume: 60μL Pressure: 2.94×10 6 Pa Flow rate: 1.00mL / min
[0083] <Synthesis of Polyurethane Acrylate B1> A 2L (liter) four-neck flask equipped with a thermometer, a stirrer, an inert gas inlet, and a reflux condenser was charged with 4000 parts by mass of polycarbonate diol (manufactured by Aldrich, number average molecular weight 2000), 238 parts by mass of 2-hydroxyethyl acrylate, 0.49 parts by mass of hydroquinone monomethyl ether, and 4.9 parts by mass of tin catalyst to prepare a reaction liquid. 666 parts by mass of isophorone diisocyanate (IPDI) was uniformly dropped into the reaction liquid heated to 70°C over 3 hours to react. After completion of the dropwise addition, the reaction was continued for 15 hours, and the time when the NCO% (NCO content) became 0.2% by mass or less was regarded as the end of the reaction, and a urethane acrylate was obtained. The NCO% was confirmed by a potentiometric automatic titrator (trade name: AT-510, manufactured by Kyoto Electronics Co., Ltd.). As a result of the analysis by GPC, the weight average molecular weight of the urethane acrylate was 8500 (standard polystyrene equivalent value). The weight average molecular weight was measured by gel permeation chromatography (GPC) using a calibration curve based on standard polystyrene under the following conditions. (Measurement conditions) Equipment: Tosoh Corporation GPC-8020 Detector: Tosoh RI-8020 Column: Gelpack GLA160S+GLA150S manufactured by Resonac Inc. Sample concentration: 120mg / 3mL Solvent: Tetrahydrofuran Injection volume: 60μL Pressure: 2.94×10 6 Pa(30kgf / cm 2 ) Flow rate: 1.00mL / min
[0084] [Preparation of film adhesive] (Examples 1 to 3, Comparative Examples 1 to 4) The components shown below were mixed in the amounts (parts by mass) shown in Table 1 to prepare respective varnish compositions.
[0085] (thermoplastic resin) A1: Polyester urethane resin (A1) synthesized as described above A2: A 40% by mass solution prepared by dissolving 40 g of bisphenol A phenoxy resin (product name: PKHC, manufactured by Union Carbide) in 60 g of methyl ethyl ketone was used (the blending amount in the table indicates the blending amount of bisphenol A phenoxy resin).
[0086] (Radical polymerizable compound) B1: Polyurethane acrylate (UA1) synthesized as described above B2: Isocyanuric acid EO modified diacrylate (product name: M-215, manufactured by Toagosei Co., Ltd.) B3: Diacrylate having a tricyclodecane skeleton (dicyclopentadiene type diacrylate) (product name: DCP-A, manufactured by Kyoeisha Chemical Co., Ltd.) B4: Pentaerythritol tetrakis(3-mercaptobutyrate) (product name: Karenz MT PE-1 ("Karenz MT" is a registered trademark), manufactured by Resonac Co., Ltd.) B5: 2-Methacryloyloxyethyl acid phosphate (product name: Light Ester P-2M, manufactured by Kyoeisha Chemical Co., Ltd.)
[0087] (Radical polymerization initiator) C1: Benzoyl peroxide (product name: Niper BMT-K40, manufactured by NOF Corporation) C2: Lauroyl peroxide (product name: Perloyl L, manufactured by NOF Corporation)
[0088] (filling material) D1: Silica fine particles (product name: R104, manufactured by Nippon Aerosil Co., Ltd., average particle size (primary particle size): 12 nm)
[0089] (Coupling Agent) E1: 3-methacryloxypropyltrimethoxysilane (product name: KBM503, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0090] The varnish composition obtained above was applied onto a PET film having a thickness of 50 μm using a coating device, and then hot air dried at 70° C. for 3 minutes to form a film-like adhesive having a thickness (thickness after drying) of 8.5 μm on the PET film.
[0091] [Evaluation of film adhesives] For the film-like adhesives produced in the Examples and Comparative Examples, evaluation of the waveform of loss tangent (tan δ), measurement and evaluation of adhesion, and measurement of adhesive strength were carried out according to the methods described below.
[0092] <Evaluation of the waveform of loss tangent (tan δ)> First, the film-like adhesive was subjected to dynamic viscoelasticity measurement in the following manner to obtain the waveform of loss tangent (tan δ). (i) A pre-heating sample is prepared by laminating a film-like adhesive to a thickness of approximately 100 μm. (ii) The pre-heated sample prepared in (i) is thermally cured using a thermocompression bonding machine "FCB3" (product name, manufactured by Panasonic) under the following conditions: backup temperature 90°C, set pressure 100N, ultimate temperature 170°C, heating time 5 seconds, to prepare a measurement sample. (iii) The measurement sample obtained in (ii) is set in a dynamic viscoelasticity measuring device "RSA-G2" (product name, manufactured by TA Instruments), and dynamic viscoelasticity is measured under the conditions of tensile mode, measurement frequency of 0.1 Hz, strain of 0.1%, heating rate of 10°C / min, and measurement temperature range of 0°C to 200°C.
[0093] Next, the number of tan δ peak tops and the presence or absence of tan δ peak bottoms were confirmed for the waveform of loss tangent (tan δ) obtained by the above dynamic viscoelasticity measurement, and based on this, the temperature difference between the tan δ peak tops and the tan δ difference between the tan δ peak bottoms and the tan δ peak tops were calculated.
[0094] <Adhesion rate measurement> The adhesion rate of the film-like adhesive was determined by the following procedure. 1.1.2 mm wide slit film adhesive is applied to a 0.7 mm thick SiN x A substrate (a glass substrate and a silicon nitride (SiN x ) and then cover the adhesive with three sheets of silicone film (thickness 200 μm). 2. Following step 1, the film-like adhesive is temporarily pressed onto the glass at 70°C, 1 MPa, and for 1 second to obtain a temporarily pressed body. 3. Photograph the temporarily bonded body from the glass side using a differential interference microscope "ECLIPSE L300" (Nikon Corporation). 4. The captured image is trimmed and binarized using a homemade program (programming language: python, using OpenCV (Intel, module name) for image processing). The trimming process is performed so that only the area where the film-like adhesive is in contact with the adherend glass remains, and the binarization process is performed so that the area where the adhesive is in close contact with the glass becomes black. Figure 5 shows an example of a binarized image of a provisionally bonded body captured by a differential interference microscope. 5. Based on the binarized image, calculate the area ratio of the black parts using the following formula, and use this as the contact ratio. Black area ratio (%) = [(number of pixels in black area) x 100] / (number of pixels in entire image)
[0095] <Evaluation of adhesion rate> If the adhesion rate measured above is within the range of 45% to 60%, good tackiness and reworkability can be obtained. If the adhesion rate is less than 45%, tackiness becomes difficult, and if the adhesion rate exceeds 60%, reworkability deteriorates.
[0096] <Adhesive strength measurement> The adhesive strength of the film-like adhesive was measured according to the following method.
[0097] A 25μm pitch COF (manufactured by FLEXSEED) and a glass substrate with thin-film electrodes (manufactured by Geomatec Co., Ltd.) having thin-film electrodes (height: 1200Å) made of silicon nitride (SiNx) on the glass substrate were connected over a width of 1mm using a thermocompression bonding device (heating method: constant heat type, manufactured by Taiyo Kikai Seisakusho Co., Ltd.) under conditions of 180°C, 4.5MPa, and 4 seconds to produce a circuit connection structure (connection structure). The adhesive strength of the obtained circuit connection structure at room temperature immediately after connection was measured using Tensilon UTM-4 (manufactured by Toyo Baldwin Co., Ltd., peel strength 50mm / min).
[0098] [Table 1] [Explanation of symbols]
[0099] 1...adhesive film, 2...adhesive component, 3...conductive particles, 4...first circuit member, 5...second circuit member, 6...connection portion, 7...insulating material, 10...connection structure, 41...first circuit board, 42...first electrode, 51...second circuit board, 52...second electrode.
Claims
1. laminating an adhesive film on a surface of a first circuit member having a first electrode on which the first electrode is formed; a step of disposing a second circuit member having a second electrode on the first circuit member laminated with the adhesive film such that the first electrode and the second electrode face each other, and thermocompressing the first and second electrodes to electrically connect the first electrode and the second electrode to each other; The adhesive film has a film-like adhesive containing a thermoplastic resin and a radical polymerizable compound, A method for producing a connection structure, wherein the film-like adhesive has a waveform of loss tangent (tan δ) obtained by dynamic viscoelasticity measurement after heating at 170° C. for 5 seconds, the waveform having multiple maximum values.
2. The method for manufacturing a connection structure according to claim 1, wherein the waveform of the loss tangent (tan δ) has a maximum value between 40°C and 90°C.
3. The method for producing a connection structure according to claim 1 or 2, wherein the waveform of the loss tangent (tan δ) has two maximum values between 40 ° C. and 100 ° C., and the difference between the two temperatures showing the maximum values is 20 ° C. or more and 50 ° C. or less.
4. The method for producing a connection structure according to claim 1 or 2, wherein the thermoplastic resin contains a polyester urethane resin and a phenoxy resin.
5. The method for producing a connection structure according to claim 1 or 2, wherein the radical polymerizable compound contains a (poly)urethane (meth)acrylate compound.
6. A film-like adhesive containing a thermoplastic resin and a radical polymerizable compound, A film-like adhesive, in which the waveform of loss tangent (tan δ) obtained by dynamic viscoelasticity measurement after heating at 170°C for 5 seconds has multiple maximum values.
7. The film-like adhesive according to claim 6, wherein the waveform of the loss tangent (tan δ) has a maximum value between 40°C and 90°C.
8. The film-like adhesive according to claim 6, wherein the waveform of the loss tangent (tan δ) has two maximum values between 40°C and 100°C, and the difference between the temperatures showing the two maximum values is 20°C or more and 50°C or less.
9. The film-like adhesive according to claim 6 , wherein the thermoplastic resin contains a polyester urethane resin and a phenoxy resin.
10. The film-like adhesive according to claim 6 , wherein the radical polymerizable compound contains a (poly)urethane (meth)acrylate compound.
11. The film adhesive according to claim 6 , further comprising conductive particles.
12. An adhesive film comprising the film-like adhesive according to any one of claims 6 to 11.
13. The adhesive film according to claim 12 , comprising a first adhesive layer made of the film-like adhesive, and a second adhesive layer made of an adhesive composition containing conductive particles.
14. a first circuit member having a first electrode; a second circuit member having a second electrode; a connection portion disposed between the first circuit member and the second circuit member, the connection portion electrically connecting the first electrode and the second electrode to each other; Equipped with A connection structure, wherein the connection portion comprises a cured product of the film-like adhesive according to claim 12.
Citation Information
Patent Citations
Thermosetting anisotropically electroconductive adhesive
JP1989113480A
Circuit connecting material, method for manufacturing circuit board using it, and circuit board
JP2002203427A
Circuit connecting material, and structure and method of connecting circuit terminal
WO1998044067A1